DUALISME YURISDIKSI PERADILAN MILITER DAN UMUM DALAM PENANGANAN PELANGGARAN HAM OLEH TNI (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The dual jurisdiction between military and civilian courts in handling human rights violations committed by members of the Indonesian National Armed Forces (TNI) presents significant challenges to the enforcement of justice and the rule of law. Military courts, under Law No. 31 of 1997, are authorized to prosecute TNI personnel, including in cases involving human rights violations. However, the system has been widely criticized for its lack of independence and transparency, which may lead to impunity. Although the Constitutional Court Decision No. 34/PUU-XI/2013 mandated that TNI members who commit general crimes, especially gross human rights violations, must be tried in civilian courts, this decision has not been fully implemented due to the absence of legislative amendments. This study uses a normative juridical approach and comparative analysis with military judicial systems in other countries. The findings highlight the urgent need for military court reform, stronger external oversight, and clear jurisdictional boundaries to ensure that victims' rights are upheld in a fair and transparent legal process.